2008
DOI: 10.1210/jc.2007-1756
|View full text |Cite
|
Sign up to set email alerts
|

A More Atherogenic Serum Lipoprotein Profile Is Present in Women with Polycystic Ovary Syndrome: A Case-Control Study

Abstract: PCOS is associated with a more pronounced atherogenic lipid profile. Furthermore, obesity and hyperandrogenism contribute to an adverse lipid profile. Finally, PCOS seems to constitute an additional risk factor for an atherogenic lipid profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
119
1
8

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(148 citation statements)
references
References 34 publications
20
119
1
8
Order By: Relevance
“…Women with polycystic ovary syndrome have an abnormal lipid profile, characterized by elevated triglyceride and reduced HDL-C levels. 104,105 In FM transsexuals, testosterone administration has been associated with a reduction in HDL-C and an increase of triglyceride levels. 83 In obese, postmenopausal women administration of nandrolone decanoate 86 causes a decrease in HDL-C and an increase in LDL-C levels.…”
Section: Lipid Profilementioning
confidence: 99%
“…Women with polycystic ovary syndrome have an abnormal lipid profile, characterized by elevated triglyceride and reduced HDL-C levels. 104,105 In FM transsexuals, testosterone administration has been associated with a reduction in HDL-C and an increase of triglyceride levels. 83 In obese, postmenopausal women administration of nandrolone decanoate 86 causes a decrease in HDL-C and an increase in LDL-C levels.…”
Section: Lipid Profilementioning
confidence: 99%
“…Several cardiovascular risk factors, including dyslipidemia (7,8), impaired glucose metabolism (9), abdominal obesity (10), and the metabolic syndrome (11), are more prevalent in PCOS women than in the general population and possibly contribute to the greater cardiovascular morbidity and mortality in PCOS. Of note, women diagnosed with PCOS according to the 1990 criteria have more adverse metabolic profile than those diagnosed according to the additional 2003 criteria (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…Piia [24] found that triacylglycerol is exchanged for cholesterol esters by activity of cholesteryl ester transfer protein. This process results in triacylglycerol enriched HDL-C which catabolized more rapidly [25]. The AMPK (AMP-activated protein kinase) is an intracellular energy and nutrient sensor [26], sterol regulatory element binding protein (SREBP) is a key regulator of intracellular lipid metabolism that it considered the substrate of AMPK, where mRNA of hepatic SREBP-2 and SREBP-1c are linked with AMPK inhibition in obesity-induced insulin-resistant, that correlates with an increase in hepatic expression of SREBP-2 and SREBP-1c and its target genes [27].…”
Section: Discussionmentioning
confidence: 99%